Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1007/s00421-010-1780-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of whole-body heat acclimation on cell injury and cytokine responses in peripheral blood mononuclear cells

Abstract: To test the hypothesis that whole-body heat acclimation (HA) would increase peripheral blood mononuclear cells' (PBMC) tolerance to heat shock (HS) and/or alter the release of cytokines (IL-1β, IL-6, IL-10 and TNF-α) to bacterial lipopolysaccharide (LPS), we heat acclimated nine subjects by exercising them for 100 min in a hot environment for 10 days. The subjects' PBMC were separated and cultured on days 1 and 10 of HA pre- and post-exercise. Pre-exercise PBMC were allocated to three treatments: control (PRE,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 37 publications
(62 reference statements)
0
25
0
Order By: Relevance
“…Consistent with this notion, we and others have demonstrated that overexpression of Hsp70 protein blocks nuclear translocation of NF-κB and thereby reduces proinflammatory mediator production (19)(20)(21)50). Although the role of Hsp70 in modulating the inflammatory response through interference with NF-κB activation has been shown in several diseases (9, [74][75][76], the link between Hsp70, NF-κB activation and cytokine production has not been established in human malaria. However, a number of previous in vitro studies have shown that hemozoin and other parasitic products…”
Section: Discussionmentioning
confidence: 51%
“…Consistent with this notion, we and others have demonstrated that overexpression of Hsp70 protein blocks nuclear translocation of NF-κB and thereby reduces proinflammatory mediator production (19)(20)(21)50). Although the role of Hsp70 in modulating the inflammatory response through interference with NF-κB activation has been shown in several diseases (9, [74][75][76], the link between Hsp70, NF-κB activation and cytokine production has not been established in human malaria. However, a number of previous in vitro studies have shown that hemozoin and other parasitic products…”
Section: Discussionmentioning
confidence: 51%
“…) and the delta change in T rec (VHOT 2.22±0.65°C), it may be more appropriate to implement an isothermic (controlled hyperthermia) model of exercise-heat exposure (Garrett et al 2009(Garrett et al , 2011(Garrett et al , 2012 where the rate of heat production can be accelerated (Amorim et al 2008) and proposed minimum endogenous temperatures targeted (Amorim et al 2011). This model requires greater exercise intensity during the early stages of the exposure, thus ensuring a more rapid increase in T rec and consequently greater change in T rec , followed by a reduction in workload once a desired temperature has been achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Research has identified extracellular changes in Hsp72 concentration within whole blood (Marshall et al 2006;Yamada et al 2007;Ogura et al 2008;Magalhães et al 2010;Périard et al 2012), and intracellular changes in total protein expression and/or gene transcription in monocytes and systemic tissue (McClung et al 2008;Selkirk et al 2009;Magalhães et al 2010;Amorim et al 2011) in response to thermal and exercise stress. Hsp72 binds with high affinity to the plasma membrane (Asea et al 2000) and up-regulates expression of pro-inflammatory cytokines, tumour necrosis factor-α, interleukin-1β and interleukin-6 in human monocytes.…”
Section: Introductionmentioning
confidence: 99%
“…144 Similarly, a 10-d acclimation program involving treadmill walking or running in a hot environment augments HSP70 content in peripheral blood mononuclear cells. 143,167,168 Elevation of HSP70 in response to high-intensity and long-term training is also found after an 11-d training program, but not in response to short or moderate intensity exercise. 146,[169][170][171][172] Besides exercise intensity, training status and the type of exercise seem to exert considerable effect on HSP70 expression.…”
Section: Exercise and Hsp70 Protein Expression In Animalsmentioning
confidence: 97%